Permainan Tradisonal Kalari untuk Melatih Perkembangan Fisik Motorik Kasar Anak Usia Dini - Mita Sari; Esperansa Mile; Nabila Nggai; Nurwila Ye’ete; Safira Darmayanti; Fitiyawati Ladiku (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Traditional games are an integral part of children's lives, providing not only pleasure but also serving as an educational tool that supports physical development, particularly in gross motor skills. This study aims to determine the effect of the traditional Kalari game on the development of gross motor skills in early childhood. The research method used is quantitative descriptive with observation techniques through checklist instruments in 9 children aged 4-5 years at Kiddi Care Kindergarten, Gorontalo City. The results showed that most children showed good gross motor development, where 10 children had met all motor indicators, such as the ability to jump, run zigzag, and maintain balance, 6 children met some of the indicators, and 2 children still showed limitations. Activities in the Kalari game provide opportunities for children to actively move, coordinate, and work together in a team, so that they can stimulate gross motor skills in a fun way. In addition, this game also instills character values ​​such as discipline, sportsmanship, and togetherness. Thus, the traditional Kalari game is very effective and worthy of being used as a learning medium to develop gross motor skills while strengthening children's character from an early age.